A kind of anti-oxidation corrosion UV glue and preparation method thereof

By adopting the collaborative design of fluorine-modified acrylate and superhydrophobic-superoleophilic surfactant in UV glue, combining the synergistic mechanism of antioxidants and light stabilizers, the technology of nano-alumina particles and polyetheramine toughening agents is used to solve the aging, hydrophobicity and toughness of UV glue in complex environments, and a significant improvement in anti-aging, anti-pollution and toughening performance is achieved.

CN119752330AInactive Publication Date: 2025-04-04东莞市博翔电子材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510057090.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing UV glues age under long-term ultraviolet irradiation and oxidative environments, lack of hydrophobicity and anti-pollution properties, and their toughness and adhesion strength perform poorly in high mechanical loads and thermal expansion/shrinkage cycles.

Method used

Through the synergy between scientific formula design and multifunctional components, the collaborative design of fluorine-modified acrylate and superhydrophobic-super-lipophilic surfactant is adopted, combined with the synergistic mechanism of the main antioxidant and auxiliary antioxidant, the uniform dispersion and composite crosslinking technology of nano-alumina particles and high-functional acrylate resin is used to introduce polyetheramine toughener to form a composite protection system and toughening network structure.

Benefits of technology

It significantly improves the aging resistance, hydrophobic resistance, adhesion strength and dimensional stability of UV glue, extends the stability of optical properties and coating life, and improves mechanical reliability and bonding stability in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752330A_ABST
    Figure CN119752330A_ABST
Patent Text Reader

Abstract

The invention relates to the field of photocurable adhesives, and discloses an anti-oxidative corrosion UV adhesive and a preparation method thereof. The UV adhesive of the invention comprises the following components: a photocurable acrylate resin, a fluorine-containing modified acrylate, an antioxidant, a light stabilizer, a super-hydrophobic-super-lipophilic surfactant, a polyetheramine toughening agent, nano-alumina particles, a photoinitiator and an active diluent. The invention significantly improves the anti-aging performance of the UV adhesive in a high ultraviolet and high-oxidation environment by synergistically blocking the oxidation path through a primary antioxidant and an auxiliary antioxidant, and combining a UV absorber and a hindered amine light stabilizer; by introducing a super-hydrophobic-super-lipophilic surfactant, the coating is endowed with ultra-low surface energy characteristics, and the hydrophobicity and anti-pollution ability are improved; by combining the flexible chain segment of the polyetheramine toughening agent with a cross-linked network, the toughness and adhesion strength of the UV adhesive are enhanced; by uniformly dispersing the modified nano-alumina particles, the thermal expansion coefficient of the coating is optimized, and the dimensional stability and weather resistance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of light-curing adhesives, in particular to an anti-oxidation and corrosion UV adhesive and a preparation method thereof. Background Art

[0002] As a light-curing adhesive, UV glue is widely used in electronic packaging, optical devices, automotive parts, and new energy power batteries. In particular, its adhesion and durability are crucial in the dispensing process of nickel sheets for new energy batteries. However, the existing UV glue technology still has significant technical bottlenecks and shortcomings when facing the application requirements of complex environments.

[0003] First of all, existing UV glue is very prone to aging under long-term ultraviolet light exposure and oxidative environment. Ultraviolet light can trigger photodegradation reactions of coating molecules, produce free radical chain reactions, lead to chemical bond breakage, and accelerate yellowing, brittleness, and even cracking of the coating. Although some technologies attempt to delay aging by adding antioxidants or light stabilizers, it is difficult to fundamentally prevent the aging path due to the single functional design. For example, antioxidants are mainly used to capture free radicals, while UV absorbers can only absorb part of the ultraviolet light. The effects of the two are limited when used independently, especially in high-temperature oxidative environments, where the coating performance still degrades rapidly. Therefore, how to synergistically utilize antioxidants and light stabilizers to construct a composite protection system to inhibit the aging process from a chemical reaction mechanism is a core challenge that is difficult to overcome with existing technologies.

[0004] Secondly, the hydrophobicity and anti-pollution properties of UV glue are generally insufficient, especially in high humidity and high pollution environments such as new energy batteries. Conventional acrylate-based materials are easy to absorb dust, oil and moisture due to their high surface energy, causing the surface performance of the coating to fail quickly. Although some technologies have tried to add surfactants to improve hydrophobicity, existing surfactants cannot form long-term stable super-hydrophobic structures in the coating, and are easily damaged by pollution or fail after long-term use. Therefore, by introducing super-hydrophobic-super-lipophilic surfactants into UV glue and using their molecular self-assembly characteristics to construct a low surface energy stable structure, it has become a potential solution to achieve lasting hydrophobicity and anti-pollution properties.

[0005] Thirdly, the toughness and adhesion strength of UV adhesives perform poorly under high mechanical loads and thermal expansion / contraction cycles. Conventional high cross-linking density acrylic resins improve the hardness of the coating, but significantly reduce flexibility, making the coating prone to cracking or adhesion failure due to mechanical stress concentration. Some technologies attempt to alleviate brittleness by introducing flexible monomers, but at the same time lead to a decrease in mechanical strength. How to maintain high mechanical strength while improving flexibility and combining flexible segments with cross-linked networks through the design of polyetheramine toughening agents is the key to improving toughness and adhesion performance.

[0006] Therefore, the present invention provides an anti-oxidation and corrosion UV adhesive and a preparation method thereof to solve the deficiencies of the prior art. Summary of the invention

[0007] Aiming at the technical bottleneck of the existing UV glue's insufficient performance in complex environments such as high ultraviolet rays, high humidity, high pollution, and high mechanical load, the present invention provides an anti-oxidation and corrosion UV glue and a preparation method thereof. Through scientific formula design and the synergistic effect of multifunctional components, the anti-aging, hydrophobic and anti-pollution properties, adhesion strength and dimensional stability of the UV glue are significantly improved, thereby solving the deficiencies of the existing technology and meeting the needs of new energy battery nickel sheet dispensing and other demanding industrial applications.

[0008] To achieve the above objectives, the present invention is implemented through the following technical scheme: an anti-oxidation and corrosion UV glue, comprising the following components in percentage by weight: Light-curing acrylate resin: 40%-60%; Fluorine-modified acrylate: 10%-20%; Antioxidant: 0.8%-3.5%; Light stabilizer: 1.0%-3.5%; Super hydrophobic-super lipophilic surfactants (such as: 3M TM FC-4430 or DOWSIL TM BY16-880): 1.5%-3.0%; Superhydrophobic-superlipophilic surfactant is a special fluorinated silicone compound. Through the introduction of fluorine segments, the surfactant can self-assemble on the surface of UV glue to form an ultra-thin molecular layer structure. This molecular layer gives the coating excellent hydrophobicity and anti-fouling ability by reducing the surface free energy, while enhancing the performance stability of UV glue in high humidity and dusty environments; the CF bond in the fluorine segment has a high bond energy (about 485kJ / mol), which makes the surfactant have excellent chemical stability under ultraviolet light and oxidative environments. Its superhydrophobicity mainly comes from the close arrangement between molecules and the extremely low surface tension (<20mN / m). In addition, the superlipophilic property enables the surfactant to quickly repel moisture and pollutants, thereby maintaining long-term cleanliness and transparency. Polyetheramine toughening agent 5%-10%; like: T-403 or BASF Polyetheramine SD-2000 The polyetheramine toughening agent forms intermolecular hydrogen bonds with the highly cross-linked acrylate in the UV adhesive system through its flexible chain segments. This flexible network structure can absorb stress under the action of external forces and extend the service life of the UV adhesive. At the same time, the highly active functional groups of the polyetheramine toughening agent can also enhance the compatibility with the base resin and avoid cracking or shedding of the colloid due to uneven interfaces; Polyetheramine molecules contain long-chain polyether groups and terminal amine groups. The polyether segments absorb mechanical stress through flexible molecular chains, reducing the brittleness of the coating; while the terminal amine groups can react with acrylate groups to form covalent bonds, thereby improving the mechanical strength and cross-linking stability of the system. In addition, the amine group can also form a strong adhesion at the dispensing interface and enhance the peel strength of the UV glue, especially in high voltage and high mechanical stress environments. Nano-alumina particles: 4%-6%; Photoinitiator: 3%-6%; Photoinitiators (such as 184 or TPO-L) absorb ultraviolet rays to generate free radicals, triggering photopolymerization reactions and accelerating the curing of UV adhesives; The use of photoinitiators ensures that UV glue cures quickly under ultraviolet light to form a high-density cross-linked network structure; Active diluent: 5%-10%; Add low-viscosity active diluents (such as propylene glycol diacrylate) to reduce the viscosity of UV glue for easy dispensing operations, and at the same time cross-link with the matrix to enhance the network structure after curing; The reactive diluent fully participates in the reaction during the light curing process, avoiding the generation of volatile organic compounds (VOCs) while optimizing the viscosity and fluidity of the colloid.

[0009] Preferably, the photocurable acrylate resin is an acrylate monomer having three or more functional groups.

[0010] Acrylate monomers with three or more functional groups can quickly generate a high cross-linking density network structure under ultraviolet light. This network can effectively prevent oxygen penetration, while improving the mechanical properties and adhesion of UV adhesives, making them stable and not prone to cracking in high voltage environments.

[0011] Preferably, the fluorine-modified acrylate is an acrylate containing a perfluorinated segment.

[0012] Fluorinated modified acrylates introduce perfluorinated segments to give UV adhesives low surface energy, improving hydrophobicity and anti-pollution capabilities. The chemical inertness of perfluorinated segments can also enhance chemical corrosion resistance.

[0013] The perfluorinated chain segment has extremely low surface free energy, which can effectively reduce the adsorption of pollutants and moisture on the coating surface. At the same time, its high chemical inertness can prevent the reaction between oxidants or corrosive substances and colloids. Preferably, the antioxidant comprises a primary antioxidant and an auxiliary antioxidant, the primary antioxidant is 2,6-di-tert-butyl-p-cresol, and the auxiliary antioxidant is tris(2,4-di-tert-butylphenyl) phosphate.

[0014] The primary antioxidant inhibits the oxidation chain reaction by capturing free radicals, while the auxiliary antioxidant blocks the oxidation pathway by decomposing peroxides. The synergistic effect of the two significantly improves the antioxidant capacity.

[0015] BHT captures free radicals and prevents the expansion of oxidation reactions, while phosphate antioxidants further reduce the generation of oxides by decomposing intermediates such as hydrogen peroxide. This dual mechanism can effectively delay the aging of UV adhesives caused by oxidation.

[0016] Preferably, the light stabilizer comprises a UV absorber and a hindered amine light stabilizer, wherein the UV absorber is 2-hydroxy-4-methoxybenzophenone, and the hindered amine light stabilizer is 2,2,6,6-tetramethylpiperidine.

[0017] UV absorbers reduce the damage of ultraviolet rays to materials by absorbing ultraviolet light and converting it into heat energy; hindered amine light stabilizers delay the aging process by blocking free radical reactions triggered by light.

[0018] Benzophenone compounds have strong ultraviolet absorption capacity, which can prevent ultraviolet light from destroying the chemical bonds in the colloid; HALS further inhibits photodegradation by reacting with free radicals generated by light to generate stable nitrogen oxide intermediates.

[0019] Preferably, the average particle size of the nano-aluminum oxide particles is less than 20 nm. The nano-aluminum oxide particles are evenly dispersed in the UV adhesive to improve the heat resistance and mechanical properties of the material and reduce the thermal expansion coefficient.

[0020] Nano-scale alumina particles have a large specific surface area and form a strong interface bond with the colloidal matrix, which can effectively block crack propagation and improve the mechanical strength of the material.

[0021] Preferably, a method for preparing an anti-oxidation and corrosion UV adhesive comprises the following steps: S1, mixing the light-curing acrylate resin and the fluorine-modified acrylate in proportion, and stirring at 300-500 rpm for 10-15 minutes; Low-speed stirring ensures that the two resins are fully mixed while avoiding the introduction of too many bubbles or the breaking of molecular chains.

[0022] S2, gradually add nano-alumina particles, and disperse them using a high-speed disperser at 2000-3000 rpm for 15-25 minutes; The high-speed disperser evenly disperses the nano-alumina particles through mechanical shear force to avoid particle agglomeration, thus forming a uniformly distributed reinforcement structure.

[0023] S3. Dissolve the antioxidant and light stabilizer in the active diluent, stir evenly, then slowly add into the system and stir at 30-40°C for 10-20 minutes; Antioxidants and light stabilizers are pre-dissolved in reactive diluents and can be dispersed more evenly into the UV adhesive, ensuring that they are evenly distributed in the curing network.

[0024] S4, adding super hydrophobic-super lipophilic surfactant, stirring at 400-600 rpm for 10-15 minutes; After the surfactant is evenly distributed, it can form a self-assembled molecular film on the surface of the UV glue, thereby improving the surface performance.

[0025] S5, adding polyetheramine toughening agent, and adding in steps at 40-50°C, stirring time is 20-30 minutes; Gradually adding toughening agents can avoid uneven cross-linking and ensure that the toughening of the colloid is maximized.

[0026] S6. After adding the photoinitiator, stir evenly and perform degassing treatment, the vacuum degree is -0.08 to -0.10 MPa, and the degassing time is 20-30 minutes; Vacuum degassing can remove bubbles remaining in the mixing process and improve the uniformity and transparency of UV glue.

[0027] S7, filter through a 5μm filter and package; Avoid premature failure of photoinitiators and ensure long-term stability of UV adhesives.

[0028] Preferably, the stirring temperature is controlled at 20-25° C., and the dispersion time in the nano-alumina particle adding step is 20 minutes.

[0029] Preferably, the degassing treatment time is 25 minutes.

[0030] Preferably, the package is sealed and stored in a light-proof container, and the storage temperature is controlled at a room temperature of 15-25°C.

[0031] The present invention provides an anti-oxidation and corrosion UV adhesive and a preparation method thereof. It has the following beneficial effects: 1. The present invention realizes the low surface energy characteristics and stable super-hydrophobic self-assembled molecular layer structure of UV glue surface by the collaborative design of fluorine-modified acrylate and super-hydrophobic-super-lipophilic surfactant. This design effectively prevents the attachment of moisture, dust and pollutants to the coating surface, significantly improves the hydrophobicity and anti-pollution ability of the coating, and maintains long-term cleanliness and optical transparency. Especially in high humidity or complex industrial environment, the coating of the present invention can still maintain excellent performance stability, compared with the phenomenon of coating failure caused by pollutant adsorption in the prior art, the present invention thoroughly solves the pollution cleaning problem after long-term use of the coating through this compounding strategy, and greatly extends the stability of optical performance and coating life.

[0032] 2. The present invention effectively inhibits the generation of free radicals and the propagation of photooxidation chain reactions at the molecular level through the synergistic mechanism of primary antioxidants and secondary antioxidants, combined with the dual protection system of UV absorbers and hindered amine light stabilizers. This dual system can simultaneously prevent UV-induced degradation reactions and the accumulation of intermediates in the oxidation pathway, so that UV glue exhibits excellent anti-aging properties and yellowing inhibition effects under high-ultraviolet and high-temperature oxidation environments. Compared with the common problems of yellowing, cracking or rapid degradation of adhesion properties in the prior art, the present invention significantly improves the weather resistance, structural integrity and reliability of UV glue by synergistically optimizing the chemical protection mechanism.

[0033] 3. The present invention utilizes the uniform dispersion and composite cross-linking technology of nano-alumina particles and high-functionality acrylic resin to form an enhanced network structure with high cross-linking density, which effectively improves the dimensional stability, mechanical stress resistance and thermal expansion resistance of the coating. The nano-alumina particles are dispersed in a refined manner to avoid the stress concentration problem caused by the agglomeration effect of traditional fillers, and maintain the overall strength and structural stability of the coating in a complex thermal cycle and mechanical load environment. Compared with the shortcomings of poor filler dispersion and easy cracking of the coating in traditional technologies, the present invention fundamentally overcomes the above problems by optimizing the particle dispersion technology and enhancing the network structure of the coating, so that the UV glue can still show excellent mechanical reliability under extreme working conditions.

[0034] 4. By introducing polyetheramine toughening agents, the present invention further optimizes the toughness, fatigue resistance and bonding stability of UV glue. The flexible segments of polyetheramine significantly reduce the brittleness of the colloid through stress absorption, while the chemical reaction between its terminal amine groups and acrylates enhances the crosslinking strength and interfacial adhesion. This design not only improves the peel strength of the UV glue, but also enables it to maintain long-term adhesion performance under complex working conditions such as high mechanical loads, thermal expansion or high voltage vibrations. Compared with the problem of UV glue in the prior art that is prone to failure or cracking under stress, the present invention provides a more reliable solution for industrial applications through the organic combination of flexible segments and crosslinked networks. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The present invention is a flow chart of the preparation method of anti-oxidation and corrosion UV adhesive. DETAILED DESCRIPTION

[0036] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Please refer to the attached Figure 1 : Embodiment 1: Weigh the raw materials according to the formula: light-curing acrylate resin ( 8413) 50%, fluorine-modified acrylate ( E-SERIES) 15%, antioxidant (2,6-di-tert-butyl-p-cresol 1.2%, tris (2,4-di-tert-butylphenyl) phosphate 1.8%), light stabilizer (2-hydroxy-4-methoxybenzophenone 1.2%, 2,2,6,6-tetramethylpiperidine 1.3%), super hydrophobic-super lipophilic surfactant (DOWSIL TM BY16-8800) 2.5%, polyetheramine toughening agent ( T-403) 8%, nano-alumina particles 5%, photoinitiator TPO-L 4%, active diluent ( SR295)8%.

[0038] Add the photocurable acrylate resin and the fluorine-containing modified acrylate into a stirring kettle, stir at room temperature, control the speed at 400 rpm, and mix for 12 minutes until they are evenly mixed.

[0039] While stirring, gradually add nano-alumina particles, adjust the stirrer to 2500 rpm, and stir at high speed for 20 minutes to ensure that the particles are completely dispersed. Visually observe that there are no obvious agglomerated particles and the colloid viscosity is moderate.

[0040] The antioxidant and light stabilizer are dissolved in the active diluent to form a uniform solution, and then slowly added to the system, maintaining a stirring speed of 400 rpm, controlling the temperature at 35°C, and stirring for 15 minutes to ensure uniform distribution.

[0041] Add the superhydrophobic-superoleophilic surfactant, adjust the stirring speed to 500 rpm, and continue stirring for 10 minutes to distribute it throughout the system and keep the fluidity stable.

[0042] Finally, the polyetheramine toughening agent was added step by step, dripped in three times, with an interval of 5 minutes each time. The total stirring time was controlled at 25 minutes and the temperature was maintained at 45°C.

[0043] After adding the photoinitiator, continue stirring at a low speed for 5 minutes to complete the mixing. Transfer to the vacuum degassing equipment, keep the degassing vacuum degree at -0.09MPa, and last for 25 minutes. The colloid is transparent and no bubbles remain.

[0044] After filtering with a 5μm filter, place in a light-proof container, seal and store at 15°C.

[0045] Embodiment 2: Prepare raw materials: light-curing acrylic resin ( 8413) 55%, fluorine-modified acrylate ( E-SERIES) 18%, super hydrophobic-super lipophilic surfactant (DOWSIL TM BY16-8800) 3.0%, nano-alumina particles 4.5%, photoinitiator 1845%, active diluent ( SR295) 7%, the remaining components include antioxidants (1.0% BHT, 1.5% phosphate), light stabilizers (1.0% benzophenone, 1.0% hindered amines), polyether amine toughening agents ( T-403)7%.

[0046] Mix the light-curable acrylic resin and the fluorinated modified acrylic and stir at 350 rpm for 15 minutes. Stir at a low speed to avoid introducing too many bubbles and ensure that the two substrates are mixed evenly.

[0047] Add nano-alumina particles and stir at high speed at 2800 rpm for 25 minutes until the particles are evenly dispersed and the appearance of the system is uniform.

[0048] After the antioxidant and light stabilizer were diluted with the active diluent, they were slowly added dropwise at 30° C. The stirring speed was controlled at 400 rpm for 18 minutes.

[0049] A superhydrophobic-superoleophilic surfactant was added, and stirring was maintained at 450 rpm for 12 minutes until the system exhibited stable fluidity.

[0050] Add polyetheramine toughening agent, raise the temperature to 40°C, add in steps, add three times, each time with an interval of 5 minutes, and the total stirring time is 30 minutes.

[0051] Add the photoinitiator, stir for 5 minutes and then degas. The vacuum degree is -0.08 MPa and the degassing time is 20 minutes.

[0052] Filter and dispense into light-proof bottles, seal and store at 20°C.

[0053] Embodiment 3: Weigh in proportion: light-curing acrylate resin ( 8413) 48%, fluorine-modified acrylate ( E-SERIES) 12%, polyetheramine toughening agent 10% ( T-403), nano-alumina particles 5%, super hydrophobic-super lipophilic surfactant (DOWSIL TM BY16-8800) 2%, photoinitiator TPO-L 4%, antioxidant combination 2.8% (BHT 1.3%, phosphate 1.5%), light stabilizer combination 2.5% (benzophenone 1.3%, hindered amine 1.2%), active diluent ( SR295)7%.

[0054] The photocurable acrylate resin and the fluorine-modified acrylate were mixed at a stirring speed of 300 rpm for 10 minutes.

[0055] Add nano-alumina particles and process with a high-speed disperser at 2000 rpm for 15 minutes to ensure that the particles are evenly dispersed. Observe the system and it is viscous but uniform.

[0056] The antioxidant and light stabilizer were diluted with active diluents respectively and added dropwise, with the stirring speed maintained at 350 rpm, the temperature controlled at 35°C, and the stirring time for 20 minutes.

[0057] Add polyetheramine toughening agent, maintain the temperature at 45°C, add dropwise in steps with an interval of 6 minutes and a total stirring time of 25 minutes.

[0058] Add superhydrophobic-superoleophilic surfactant and photoinitiator and stir at low speed for 5 minutes to complete mixing.

[0059] Perform vacuum degassing at a vacuum degree of -0.09 MPa for 30 minutes. Filter after degassing, filter with a 5 μm filter, and dispense into sealed containers at a storage temperature of 25°C.

[0060] Comparative Example: Comparative Example 1: Weigh the raw materials according to the following proportions: Light-curing acrylate resin ( 8413)60% Fluorinated modified acrylate is not added Antioxidant (2,6-di-tert-butyl-p-cresol 1.0%, tris(2,4-di-tert-butylphenyl) phosphate 1.5%) No light stabilizer added Super hydrophobic-super lipophilic surfactant (DOWSIL TM BY16-8800)1.0% Polyetheramine toughening agent ( T-403) 5% Nano-alumina particles 3% Photoinitiator TPO-L3% Active diluent ( SR295)6% Processing technology: Mixing resin: Add light-curing acrylate resin into the stirring kettle, stirring speed 300rpm, stirring time 8 minutes, to ensure the substrate is uniform.

[0061] Add nano-alumina particles: gradually add nano-alumina particles and stir with a high-speed disperser at 2000 rpm for 15 minutes. Since the amount of particles is low, it is only necessary to ensure that the dispersion is basically uniform.

[0062] Add antioxidant and diluent: Add antioxidant and active diluent after mixing evenly, stir at 400 rpm, control temperature at 35°C, and stir for 10 minutes.

[0063] Add superhydrophobic-superoleophilic surfactant: add slowly at low speed (300 rpm) and stir for 6 minutes. The surfactant is not evenly distributed.

[0064] Add toughening agent: polyetheramine toughening agent is added twice, each time with an interval of 5 minutes, the total stirring time is 15 minutes, and the stirring temperature is maintained at 35°C to save energy.

[0065] Adding photoinitiator: After adding the photoinitiator, stir for 5 minutes and perform a simple degassing treatment (vacuum degree is only -0.06MPa, time is 15 minutes).

[0066] Filtration and storage: Filter with a 10μm filter (the particle filtration effect is poor), seal in a light-proof container, and maintain the storage temperature at 25℃.

[0067] Comparative Example 2: Raw material composition: Light-curing acrylate resin ( 8413)55% Fluorinated modified acrylate( E-SERIES) 12% Antioxidant (2,6-di-tert-butyl-p-cresol 1.0%, tris(2,4-di-tert-butylphenyl) phosphate 1.5%) Light stabilizer (2-hydroxy-4-methoxybenzophenone 1.0%, 2,2,6,6-tetramethylpiperidine 1.0%) Polyetheramine toughening agent ( T-403)8% Nano-alumina particles 3% Photoinitiator 1844% Active diluent ( SR295)8% Features: Omit super hydrophobic-super lipophilic surfactant.

[0068] Processing technology: Mixing resin: Mix the light-curing acrylate resin and the fluorine-modified acrylate, stir at a low speed of 400 rpm for 12 minutes, and make the system uniform.

[0069] Add nano-alumina particles: gradually add nano-alumina particles, use a high-speed stirrer at 2500 rpm, and continue stirring for 20 minutes to ensure uniform dispersion and no obvious agglomeration by visual inspection.

[0070] Add antioxidant and light stabilizer: After dissolving the antioxidant and light stabilizer in the active diluent, add them dropwise into the system, stir at a speed of 450 rpm, control the temperature at 35°C, and stir for 15 minutes.

[0071] Add toughening agent: polyetheramine toughening agent is added dropwise three times, stirring at 45°C, with an interval of 5 minutes between each addition and a total stirring time of 30 minutes to ensure uniform distribution.

[0072] Adding photoinitiator and degassing: After adding the photoinitiator, stir for 5 minutes and vacuum degassing (vacuum degree -0.08MPa, 20 minutes).

[0073] Filtration and storage: Filter with a 5μm filter, dispense into light-proof containers, seal and store at 25°C.

[0074] Comparative Example 2: Raw material composition: Light-curing acrylate resin ( 8413)55% Fluorinated modified acrylate( E-SERIES) 10% Antioxidant (2,6-di-tert-butyl-p-cresol 1.0%, tris(2,4-di-tert-butylphenyl) phosphate 1.5%) Light stabilizer (2-hydroxy-4-methoxybenzophenone 1.2%, 2,2,6,6-tetramethylpiperidine 1.0%) Polyetheramine toughening agent ( T-403)8% Nano-alumina particles 3% Photoinitiator ( 184)4% Active diluent ( SR295)8% Superhydrophobic-superlipophilic surfactant: omitted Processing technology: Mixed resin: Mix the light-curing acrylate resin with the fluorine-modified acrylate and stir at a low speed of 400 rpm for 12 minutes to ensure that the base materials are evenly mixed.

[0075] Adding nano-alumina particles: Nano-alumina particles were gradually added and stirred at 2500 rpm for 20 minutes using a high-speed stirrer. The system was observed to show no obvious agglomeration and was evenly dispersed.

[0076] Adding antioxidants and light stabilizers: After dissolving the antioxidant and light stabilizer in the active diluent, slowly add them into the system by dropwise addition, control the temperature at 35°C, stir at 450 rpm, and stir for 15 minutes.

[0077] Adding polyetheramine toughening agent: The polyetheramine toughening agent was added dropwise three times, the temperature was maintained at 45°C, the interval between each addition was 5 minutes, and the total stirring time was 30 minutes.

[0078] Addition of photoinitiator: The photoinitiator was added last, and vacuum degassing was performed after stirring for 5 minutes, with a vacuum degree of -0.08MPa and a degassing time of 20 minutes.

[0079] Filtration and storage: Filter with a 5μm filter, bottle and store away from light at 25°C.

[0080] Comparative Example 3: Raw material composition: Light-curing acrylate resin ( 8413)65% Ordinary acrylate (propylene glycol diacrylate SR295) 10% Antioxidant (2,6-di-tert-butyl-p-cresol 1.3%, tris(2,4-di-tert-butylphenyl) phosphate 1.7%) Light stabilizer (2-hydroxy-4-methoxybenzophenone 1.3%, 2,2,6,6-tetramethylpiperidine 1.2%) Super hydrophobic-super lipophilic surfactant (DOWSIL TM BY16-8800) 1.5% Polyetheramine toughening agent ( T-403) 5% Nano-alumina particles 3% Photoinitiator (TPO-L) 4% Active diluent ( SR295)6% Processing technology: Mixed resin: The light-curing acrylate resin was mixed with the common acrylate and stirred at a low speed of 350 rpm for 10 minutes until the system was uniform and no obvious bubbles were observed.

[0081] Adding nano-alumina particles: Nano-alumina particles were gradually added and stirred at 2000 rpm with a high-speed stirrer for 15 minutes to ensure that the particles were evenly dispersed and the system had a uniform appearance.

[0082] Adding antioxidants and light stabilizers: After the antioxidant and light stabilizer are dissolved in the active diluent, they are slowly added dropwise to the system with a stirring speed of 400 rpm and a temperature controlled at 35° C. for 15 minutes.

[0083] Adding superhydrophobic-superoleophilic surfactant: Add the superhydrophobic-superoleophilic surfactant and stir at 450 rpm for 10 minutes to ensure uniform distribution.

[0084] Adding polyetheramine toughening agent: The polyetheramine toughening agent was added dropwise three times, the stirring temperature was controlled at 40°C, and the total stirring time was 20 minutes to ensure that the toughening agent was completely dispersed.

[0085] Adding photoinitiator and degassing: After adding the photoinitiator, the mixture was stirred for 5 minutes and vacuum degassing was performed (vacuum degree -0.08 MPa, time 25 minutes).

[0086] Filtration and storage: Filter with a 5μm filter, bottle and store away from light at 20°C.

[0087] Test experiment: Experimental Preparation Sample preparation: According to the formula and process of Example 1, Example 2, Example 3 and Comparative Example 1, Comparative Example 2, Comparative Example 3, UV glue samples were prepared, and the following test samples were prepared respectively: Coated film samples (50 μm thick, for anti-aging, anti-pollution and dimensional stability tests).

[0088] The sample for adhesive bonding (for adhesion performance test) uses a nickel sheet (10 mm × 10 mm) as the substrate.

[0089] The prepared samples were placed in light-proof sealed containers and stored at 15°C.

[0090] Equipment and instruments: Anti-aging performance: UV accelerated aging box, spectrophotometer, electronic tensile testing machine, optical microscope.

[0091] Anti-pollution performance: contact angle measuring instrument, infrared imager, high temperature and high humidity environmental chamber.

[0092] Adhesion performance: shear strength tester, fatigue testing machine, constant temperature and humidity chamber.

[0093] Dimensional stability: Thermomechanical Analyzer (TMA), Thermal Shock Tester, Scanning Electron Microscope (SEM).

[0094] Surface morphology and structure analysis: atomic force microscopy (AFM) and water contact angle dynamic analyzer.

[0095] Environmental conditions: The room temperature was controlled at 20-25°C, the relative humidity was 40-50%, and the test water was deionized water.

[0096] Experimental procedures Anti-aging performance test objectives: To evaluate the yellowing, mechanical properties and surface microstructure changes of samples in UV and oxidative environments.

[0097] Accelerated aging test: Using an ultraviolet accelerated aging box, the coated film samples were placed under conditions of a light intensity of 365 nm, a temperature of 50° C., and a humidity of 50%, with 10 pieces per group.

[0098] The test cycle is 500 hours, sampling is performed every 100 hours, and the following performance is recorded: Yellowing Index (YI): Detected using a spectrophotometer.

[0099] Tensile strength retention rate: Before and after aging, the tensile strength was measured using an electronic tensile testing machine.

[0100] Surface crack observation: Microcracks were observed using an optical microscope and a scanning electron microscope (SEM).

[0101] Infrared spectroscopy (FTIR): Evaluate the material degradation mechanism through changes in molecular vibration.

[0102] Data analysis: Compare the yellowing index, mechanical properties and surface structure changes of the embodiment and the comparative example, and analyze the difference in anti-aging performance.

[0103] Anti-fouling performance test objectives: To evaluate the sample's hydrophobicity, anti-fouling properties and surface cleaning ability.

[0104] Water contact angle test: Initial contact angle: Use a contact angle meter to measure the static water contact angle of the sample surface, repeat 10 times and take the average value.

[0105] Dynamic contact angle: Use a dynamic contact angle analyzer to test the sliding angle and hysteresis angle to evaluate the surface hydrophobicity uniformity.

[0106] Anti-fouling ability test: Mixed pollutants (silicone oil, dust and mud solution) were dripped onto the sample surface, left at room temperature for 24 hours, then rinsed with deionized water, and the cleaning effect was observed using an optical microscope.

[0107] The residual distribution of pollutants on the sample surface is detected by infrared imaging and the cleaning rate is calculated.

[0108] Long-term cleanliness test: The samples were placed in a high humidity (RH 90%) and high temperature (50° C.) environment for 14 days, and the water contact angle and antifouling tests were repeated.

[0109] Adhesion performance test objective: To verify the bonding strength and fatigue resistance of UV glue in the dispensing process of nickel sheets for new energy batteries.

[0110] Bond Strength: Nickel sheet (10mm×10mm) was glued and then UV cured for 30 seconds (365nm, 5mW / cm 2 ), test the initial shear strength.

[0111] After being placed in a constant temperature and humidity chamber (25°C, RH 60%) for 7 days, the bonding strength was re-measured.

[0112] Fatigue performance: The bond strength retention was tested after 1000 cycles of compression-tension (0.1-10N) using a fatigue testing machine.

[0113] The microstructure of the interfacial bonding after fatigue was observed using SEM.

[0114] Dimensional stability test objective: To evaluate the thermal expansion and cracking risk of UV adhesive in high and low temperature environments.

[0115] Thermal expansion test: 50 μm thick film samples were prepared and the linear thermal expansion coefficient (CTE) was measured using TMA in the temperature range of -40°C to 100°C.

[0116] Hot and cold cycle shock: The dispensing samples were placed in a thermal shock tester (-40°C to 85°C, 30 minutes per cycle, 100 times in total), and SEM was used to observe whether the coating cracked or fell off.

[0117] Detect the integrity of the interface between the colloid and the nickel sheet.

[0118] Experimental data: Table 1: Comprehensive performance test data of anti-oxidation and corrosion UV adhesive The comprehensive performance of the examples fully demonstrates the superiority of the technical solution. In particular, in terms of anti-aging performance, the examples show extremely low yellowing index and high strength retention rate. This stability is attributed to the synergistic effect of antioxidants and light stabilizers, which prevents the further expansion of free radical chain reactions, and the capture ability of hindered amine light stabilizers plays a key role. However, the single anti-aging design in the comparative example cannot achieve this complex molecular synergistic effect, resulting in a significant increase in cracks after aging.

[0119] The results of anti-pollution performance further verified the innovative design of super-hydrophobic-super-lipophilic surfactant. The ultra-low surface energy molecular layer formed by the self-assembly of the surfactant not only gives the coating excellent anti-fouling cleaning properties, but also maintains stable hydrophobic properties in a long-term high-humidity environment. The comparative example lacks this design, causing its hydrophobic performance to drop rapidly, with a high residual rate of pollutants, and the coating surface cannot be kept clean for a long time.

[0120] The dimensional stability test reveals the excellent performance of the examples in complex environments. The flexible segments of the polyetheramine toughening agent absorb mechanical stress, while the nano-alumina particles play a core role in dispersion enhancement and thermal expansion inhibition. The optimized design of this composite network allows the UV glue to maintain integrity during hot and cold cycles, avoiding cracking and falling off in the comparative examples. This unpredictable performance improvement significantly enhances the durability and reliability of the colloid.

[0121] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An anti-oxidation and corrosion UV adhesive, characterized in that: The composition includes the following components in weight percentage: Light-curing acrylate resin: 40%-60%; Fluorine-modified acrylate: 10%-20%; Antioxidant: 0.8%-3.5%; Light stabilizer: 1.0%-3.5%; Super hydrophobic-super lipophilic surfactant: 1.5%-3.0%; Polyetheramine toughening agent: 5%-10%; Nano-alumina particles: 4%-6%; Photoinitiator: 3%-6%; Active diluent: 5%-10%.

2. The anti-oxidation and corrosion UV adhesive according to claim 1, characterized in that: The photocurable acrylate resin is an acrylate monomer having three or more functional groups.

3. The anti-oxidation and corrosion UV adhesive according to claim 1, characterized in that: The fluorine-containing modified acrylate is an acrylate containing a perfluorinated segment.

4. The anti-oxidation and corrosion UV adhesive according to claim 1, characterized in that: The antioxidant comprises a main antioxidant and an auxiliary antioxidant, wherein the main antioxidant is 2,6-di-tert-butyl-p-cresol, and the auxiliary antioxidant is tris(2,4-di-tert-butylphenyl)phosphate.

5. The anti-oxidation and corrosion UV adhesive according to claim 1, characterized in that: The light stabilizer comprises a UV absorber and a hindered amine light stabilizer, wherein the UV absorber is 2-hydroxy-4-methoxybenzophenone, and the hindered amine light stabilizer is 2,2,6,6-tetramethylpiperidine.

6. The anti-oxidation and corrosion UV adhesive according to claim 1, characterized in that: The average particle size of the nano-alumina particles is less than 20 nm.

7. The method for preparing an anti-oxidation and corrosion UV adhesive according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, mixing the light-curing acrylate resin and the fluorine-modified acrylate in proportion, and stirring at 300-500 rpm for 10-15 minutes; S2, gradually add nano-alumina particles, and disperse them using a high-speed disperser at 2000-3000 rpm for 15-25 minutes; S3. Dissolve the antioxidant and light stabilizer in the active diluent, stir evenly, then slowly add into the system and stir at 30-40°C for 10-20 minutes; S4, adding super hydrophobic-super lipophilic surfactant, stirring at 400-600 rpm for 10-15 minutes; S5, adding polyetheramine toughening agent, and adding in steps at 40-50°C, stirring time is 20-30 minutes; S6. After adding the photoinitiator, stir evenly and perform degassing treatment, the vacuum degree is -0.08 to -0.10 MPa, and the degassing time is 20-30 minutes; S7, filter through a 5μm filter and package.

8. The method for preparing an anti-oxidation and corrosion UV adhesive according to claim 7, characterized in that: The stirring temperature is controlled at 20-25° C., and the dispersion time in the nano-alumina particle adding step is 20 minutes.

9. The method for preparing an anti-oxidation and corrosion UV adhesive according to claim 7, characterized in that: The degassing treatment time is 25 minutes.

10. The method for preparing an anti-oxidation and corrosion UV adhesive according to claim 7, characterized in that: The package is sealed and stored in a light-proof container, and the storage temperature is controlled at a normal temperature of 15-25°C.